2021
DOI: 10.1186/s13071-021-04793-4
|View full text |Cite
|
Sign up to set email alerts
|

Recent aspects on epidemiology, clinical disease, and genetic diversity of Toxoplasma gondii infections in Australasian marsupials

Abstract: Background Toxoplasma gondii infections are common in humans and animals worldwide. Among all intermediate hosts of T. gondii, captive marsupials from Australia and New Zealand are highly susceptible to clinical toxoplasmosis. However, most free-range marsupials establish chronic T. gondii infection. Infected marsupial meat may serve as a source of T. gondii infection for humans. Differences in mortality patterns in different species of kangaroos and other marsupials are not fully understood. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(34 citation statements)
references
References 29 publications
2
31
0
1
Order By: Relevance
“…Therefore, striated muscle, spleen, kidney liver, lungs, and brain could be selected to isolate T. gondii . This finding is consistent with other reports on cats or macropods ( Dubey et al, 2020 , 2021 ). Parasite load may be related to animal species, infection status, strain, or genotypes of T. gondii and the environment.…”
Section: Discussionsupporting
confidence: 94%
“…Therefore, striated muscle, spleen, kidney liver, lungs, and brain could be selected to isolate T. gondii . This finding is consistent with other reports on cats or macropods ( Dubey et al, 2020 , 2021 ). Parasite load may be related to animal species, infection status, strain, or genotypes of T. gondii and the environment.…”
Section: Discussionsupporting
confidence: 94%
“…This is the first time that this genotype is reported in macropods, and, given the histopathological findings, it could be considered virulent for this species. Although the isolate had a majority of type III alleles for the 10 standard markers, and type III alleles are considered to have low virulence in mice, a clonal type III caused disseminated toxoplasmosis and death in M. rufus, M. rufogriseus and M. eugenii from Argentina and the USA ( 26 , 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Even though these two wallabies were treated with Sulfadoxine/Trimethoprim and Clindamycin, they were not effective, and both animals died. Currently none of the treatments described to treat toxoplasmosis in macropods has proven to be effective and the variability of the treatment response could be subject to the specific genotype that caused the clinical signs ( 8 , 27 ). It has been suggested that the exhibits of macropods and other susceptible species must have a good water drainage, in order to avoid water stagnation and prevent storm water (that could be carrying oocysts) from running into the exhibits ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been speculated that since Australian marsupials evolved in the absence of cats they therefore are thought to be more susceptible to toxoplasmosis 2 . Vertical transmission has also been proven to occur in marsupials, though infections in the joey may be subclinical 3,9 . It has also been shown that those that are immune compromised or stressed can have increased susceptibility to clinical manifestation of the disease.…”
Section: Discussionmentioning
confidence: 99%